Characteristics of and Factors Influencing College Nursing Students' Willingness to Utilize mHealth for Health Promotion. Issue 5 (May 2020) - Sittig, Scott; Hauff, Caitlyn; Graves, Rebecca J.; Williams, Susan G.; McDermott, Ryon C.; Fruh, Sharon; Hall, Heather; Campbell, Matt; Swanzy, Debra; Wright, Theresa; Hudson, Geoffrey M.
Abstract : More than half of practicing nurses have suboptimal physical or mental health. Impaired health is associated with a 76% higher likelihood that nurses will make medical errors. Improving the health habits of nursing students is essential to shaping and sustaining health prior to joining the workforce. Technology such as mobile health applications holds great promise in facilitating behavioral change and encouraging healthy habits in nursing students. Identifying the predictors of willingness to use mobile health is essential to creating mobile health applications that will engage nursing students and promote sustainable usage. Evaluation of psychological, attitudinal, and health-related correlates of mobile health can highlight predictors of willingness to use mobile health, which can influence nursing students' utilization and long-term engagement with mobile health applications. Analysis of these correlates shows that psychological attributes, such as hope, play a role in the willingness to use and may facilitate engagement in the utilization of a mobile health application. Development of a mobile health application that increases hope and helps establish healthy habits may enable nursing students to remain healthy throughout their lives, creating a new generation of happier, healthier nurses and, ultimately, improving safety for patients under their care.